Secreted Trypanosome Cyclophilin Inactivates Lytic Insect Defense Peptides and Induces Parasite Calcineurin Activation and Infectivity - Kulkarni, Manjusha M.; Karafova, Anna; Kamysz, Wojciech; Schenkman, Sergio; Pellé, Roger; McGwire, Bradford S. (Elsevier, 2013)
The mechanisms by which Trypanosoma cruzi survives antimicrobial peptides and differentiates during its transit through the gastrointestinal tract of the reduviid vector are unknown. We show that cyclophilin, a peptidyl-prolyl isomerase secreted from T. cruzi epimastigotes, binds to and neutralizes the reduviid antimicrobial peptide trialysin promoting parasite survival. This is dependent on a singular proline residue in trialysin and is inhibited by the cyclophilin inhibitor cyclosporine A. In addition, cyclophilin-trialysin complexes enhance the production of ATP and reductase responses of parasites, which are inhibited by both calcineurin-specific inhibitors cyclosporine A and FK506. Calcineurin phosphatase activity of cyclophilin-trialysin-treated parasites was higher than in controls and was inhibited by preincubation by either inhibitor. Parasites exposed to cyclophilin-trialysin have enhanced binding and invasion of host cells leading to higher infectivity. Leishmanial cyclophilin also mediates trialysin protection and metabolic stimulation by T. cruzi, indicating that extracellular cyclophilin may be critical to adaptation in other insect-borne protozoa. This work demonstrates that cyclophilin serves as molecular sensor leading to the evasion and adaptive metabolic response to insect defense peptides.